利用牛津研究体系深化对中国青铜器的认识 : Applying the Oxford System to further understand bronzes in China - Pollard, A; Bray, P; Hommel, P; Hsu, Y; Liu, R; Rawson, J (Institute of Archaeology Chinese Academy of Social Sciences, 2017)
In recent years, the Research Laboratory for Archaeology and History of Art in the University of Oxford has developed a systematic approach to metal chemistry designed to characterize, using trace elements, alloying elements and lead isotopes in an assemblage of material, the underlying flow of metal. The primary objective of this paper is to present its fundamental principal, stepwise analysis meaning and a number of preliminary results from its application to Shang and Western Zhou China and some associated regions. The characterization in this paper has brought new light to a series of archaeologically meaningful issues on copper flow between Zhengzhou and Panlongcheng, remelting objects during the interaction between central China and the Steppe, the provenance and dynamic mechanism of copper and lead supply from Erlitou/Erligang, Anyang to Western Zhou. More importantly, it enables scholars to combine more easily archaeological information and scientific data and ask new questions. 近几年，牛津大学考古与艺术史实验室摸索出一套系统的方法，通过利用铜器微量元素、合金元素以及铅同位素来表征背后的金属流通。本文主旨在于阐述这一方法的基本原理、具体操作步骤以及将其运用至商周时期的中国以及相关地区时所得到的初步结论。本文所介绍的表征方法为研究一系列重要的考古学问题带来了新的视角，包括郑州、盘龙城之间的铜料流通，中原与草原在交流过程中的铜器回收重熔，在二里头/二里冈、安阳时期以及西周时期的铜、铅的矿料来源以及供应体系的变化。更重要的是，这一方法可以让学者更加有效地将考古信息与科学分析数据结合在一起，从而提出新的研究问题。